2015
DOI: 10.3126/jcmc.v4i3.11936
|View full text |Cite
|
Sign up to set email alerts
|

Patients' satisfaction with hospital services in Kathmandu

Abstract: Patient satisfaction is valid indicator for measurement of service quality. Patient's opinions are important because dissatisfaction suggests opportunities for improvement of health services in the hospital. The objective of this study was to assess the patient satisfaction with hospital services. Descriptive survey study design was adopted for this study .The population of the study was the clients who have been inpatient in Tribhuvan University Teaching Hospital (TUTH) in Kathmandu. Non probability purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…7 Subedi D et al concluded in a study conducted in the Institute of Medicine, Nepal that patients were highly satisfied with the technical competencies of doctors and nurses. 8 Socio-demographic characteristics were concluded by some studies to be at best a minor predictor of satisfaction. 8 Patient demographics such as age, gender, income, socioeconomic and general health status impact patients' responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Subedi D et al concluded in a study conducted in the Institute of Medicine, Nepal that patients were highly satisfied with the technical competencies of doctors and nurses. 8 Socio-demographic characteristics were concluded by some studies to be at best a minor predictor of satisfaction. 8 Patient demographics such as age, gender, income, socioeconomic and general health status impact patients' responses.…”
Section: Discussionmentioning
confidence: 99%
“…8 Socio-demographic characteristics were concluded by some studies to be at best a minor predictor of satisfaction. 8 Patient demographics such as age, gender, income, socioeconomic and general health status impact patients' responses. 9 Beyond these obvious characteristics, many other factors such as primary language, parental status, sexual orientation, values, beliefs, or communication style may be associated.…”
Section: Discussionmentioning
confidence: 99%
“…Subedi D, et al at Kathmandu Hospital study reveals that 54.1% of respondents answered that they were fairly satisfied with communication with nurse, 71.6% were often satisfied with answer of respondents questions, 68.5% mentioned that nurses often treat them in a friendly way, 49% mentioned that doctor explained about ongoing treatment and they were often satisfied with it. 9 In a study from the outpatient department of a private medical college hospital at Manglore on consumer satisfaction, it was shown that 66.7% mentioned that they were fairly satisfied with respect given by other staff of the hospital, and 58.1% answered that they were occasionally satisfied with receptionists answer about their query. 15 One of the study conducted by Sadjadian et al, 'Patient satisfaction: a descriptive study of a breast care clinic in Iran' reported that majority of the respondents were satisfied with skill of nurses and doctor.…”
Section: Discussionmentioning
confidence: 99%
“…8 Nearly similar result was found in the study conducted by Subedi D, et al at a teaching hospital at Kathmandu, where almost half 52.7% of the respondent were male, 34.23% of respondents were age group between 46 to 60 years. 9 Considering the determinants of good clinical governance, clinicians have to learn to improve skills of communication alongside their clinical skills. Study by Shahzadi et al at a Peshawar Hospital showed that majority of patients were not satisfied with the way their doctor greeted them, only 5.90% were called by their names.…”
Section: Discussionmentioning
confidence: 99%
“…Page 921 Majority i.e.190 (38%) of patients were males while 310 (62%) of patients were females.Similar to present study, D Subedi et al, found that 34.23% of respondents were in the age group of 46-60 years whereas 14.86% were of 16-30 years of age. 52.70% of the respondents were male 11. …”
mentioning
confidence: 97%